DEVELOPMENT OF A CANVA-BASED MATHEMATICS TEACHING E-MODULE TO FACILITATE JUNIOR HIGH SCHOOL STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITIES ON ALGEBRAIC FORMS: Riau, Indonesia - Ranny Mukerdi; Reni Wahyuni; Indah Widiati; Sindi Amelia (Jurnal Math-UMB.EDU, 2025)
This study aims to produce a product in the form of a Canva-based teaching e-module to facilitate creative thinking skills in algebraic form material. This study uses a Research and Development (R&D) approach with stages, namely potential and problems, data collection, product design, design validation, design revision, product testing, product revision, and final product. In the data collection process, researchers used several instruments in the form of validation sheets addressed to experts, as well as practicality questionnaires intended for teachers and students. The objects of this study were eighth grade students at the junior high school level. Based on the development results, it was obtained that the learning media in the form of teaching e-modules designed by using the Canva platform showed validation results with an average percentage value of 85.47% with valid criteria. Meanwhile, the practicality value obtained from the teacher's practicality questionnaire was with an average percentage of 87.5% with very practical criteria, and the student's practicality questionnaire with an average percentage value of 88.89% with very practical criteria. Thus, the results of the research and development of Canva-based teaching e-modules for creative thinking skills in algebraic form material for junior high school students can be concluded that from the validation results by experts and responses from teachers and students, the developed learning media is declared suitable for use in the learning process. Keywords : e-learning module, Canva, creative thinking.